Clinical epidemiology of cardiovascular disease in advanced chronic kidney disease prior to dialysis to a tertiary care centre in Bangladesh - Ali, Md Yousuf; Rahman, Aminur; Zakia, Kazi Ismat; Paul, Sanjoy Kumar; Mim, Maisha Zerin (Bangladesh Journal of Medicine, 2024)
Background: Patients with advanced CKD stages exhibit a markedly elevated risk of cardiovascular disease. Patients with chronic kidney disease (CKD) exhibit an elevated cardiovascular risk manifesting as coronary artery disease, heart failure, arrhythmias, and sudden cardiac death .The main objective of this study was to observe the clinical epidemiology of cardiovascular disease in advanced stages of CKD prior to dialysis to a tertiary care centre in Bangladesh. Methods: This was a cross-sectional observational study on 150 cases of diagnosed advanced stages (4&5) of CKD patients in the indoor Department of Medicine of Sir Salimullah Medical College Mitford Hospital, Dhaka, Bangladesh from July 2022to January2023 for 6 months. Data was analyzed SPSS 25. Results: Out of the total group, 62.0% are male, 38.0% are female, and the average (mean) age of the entire group was 55.2 ±10.3. Patients are compared in terms of their relative percentages and the associated cardiovascular disease (CVD) risk, with the hypothesis that lower hemoglobin levels (<9 mg/dL), common in advanced CKD, may be associated with higher CVD risk. A statistically significant P-value (0.036) indicates a significant association between lower hemoglobin levels and increased risk of CVD. Hypertension is the most common risk factor in both stages showing (80%) in stage 4 and 86.6% in Stage -5 of CKD respectively that increasing prevalence as stages of CKD increases . Other factors like diabetes 50.6%) and 53.3% , dyslipidemia 61.3% and 66.7% , and family history of cardiovascular disease (CVD) 40% and 46.6% also in prevalence from Stage 4 to Stage 5. However, the differences in the prevalence of these risk factors between the two stages are not statistically significant, as indicated by the P-values. The prevalence of Congestive Heart Failure rises from 44% in Stage 4 to 52% in Stage 5, and a similar trend is observed in Coronary Artery Disease from 40% in Stage 4 to 48% in Stage 5 and for other diseases, albeit with lesser increments. The provided pvalues, which assess statistical significance, indicate that the differences in disease prevalence between the two stages are not statistically significant, suggesting that the progression from Stage 4 to Stage 5. Conclusion: This study stated that increased prevalence and progression of cardiovascular risks in advanced CKD stages. Bangladesh J Medicine 2024; 35: 96-100